PERITONEAL DIALYSIS IN NEWBORNS AND INFANTS IN THE LAST 20 YEARS: SINGLE CENTER EXPERIENCE - Bağdagül Yavaş Aksu; Zeynep Nagehan Yürük Yıldırım; Meltem Bor; Beril Yaşa; Leyla Bilgin; Nevin Uygur; Alev Yılmaz (İstanbul Tıp Fakültesi Dergisi)
Objective: To evaluate patients who underwent acute and chronic peritoneal dialysis under the age of one one in terms of etiology, complications, and prognosis over 20 years and to compare the results between the first and last 10 years of acute and chronic peritoneal dialysis.Material and Method: Seventy-four peritoneal dialysis patients under the age of one in the Division of Pediatric Nephrology and Neonatal Intensive Care Unit of our hospital between January 2002 and December 2023 were evaluated retrospectively. The patients were divided into two groups: patients admitted in the 2002-2013 period (Group I) and patients admitted in the 2013-2023 period (Group II). Patients in Group I and Group II were compared in terms of acute and chronic peritoneal dialysis etiology, complications, and prognosis.Result: Forty-four of the patients (60%) were newborns, and the remaining 30 were infants (40%). There were 39 patients in Group I and 35 patients in Group II. There was no difference between Group I and Group II for acute dialysis in terms of neonatal and infant diagnoses, infectious and non-infectious complications, and prognosis (p>0.05). There was no difference between Group I and Group II in terms of neonatal and infant diagnoses, infectious and non-infectious complications, and infant prognosis (p>0.05). There was no death in the newborns in Group II and patient survival was higher than in the newborns in Group I (p=0.019).Conclusion: Peritoneal dialysis is the most commonly used method for renal replacement therapy in children facing both acute and chronic renal failure. In the last decade, despite high-quality care in the neonatal care unit, positive technological developments and effective management of PD, the most common infectious complication was still peritonitis, and the non-infectious complication was dialysate leakage, as in the previous 10 years.